1993
DOI: 10.1002/ajmg.1320460110
|View full text |Cite
|
Sign up to set email alerts
|

Human smooth muscle myosin heavy chain gene mapped to chromosomal region 16q12

Abstract: The partial nucleotide sequence encoding the rod portion of the entire amino acid sequence of human smooth muscle myosin heavy chain (MHC) which corresponds to MYH11, according to Human Gene Mapping nomenclature, has been determined by cloning a complementary DNA (cDNA) and sequencing the cDNA (UMYHSM). Northern blot analysis with the UMYHSM fragment (4.3 Kb) showed that the smooth muscle MHC of the human umbilical artery is expressed in the human umbilical artery, bladder, esophagus and trachea. Southern blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 15 publications
(1 reference statement)
2
40
0
Order By: Relevance
“…We provide evidence for immunological cross-reactivity as a mechanism for the generation of SMA and ANA in chronic HCV [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 2·11 ± 0·61 2·09 ± 0·49 0·97 HCV-pol [1479][1480][1481][1482][1483][1484][1485][1486][1487][1488][1489][1490][1491][1492][1493][1494][1495][1496][1497][1498] 2·33 ± 0·63 2·72 ± 0·95 0·14 Matrin [722][723][724][725][726][727][728][729][730][731][732][733][734][735][736][737][738]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We provide evidence for immunological cross-reactivity as a mechanism for the generation of SMA and ANA in chronic HCV [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 2·11 ± 0·61 2·09 ± 0·49 0·97 HCV-pol [1479][1480][1481][1482][1483][1484][1485][1486][1487][1488][1489][1490][1491][1492][1493][1494][1495][1496][1497][1498] 2·33 ± 0·63 2·72 ± 0·95 0·14 Matrin [722][723][724][725][726][727][728][729][730][731][732][733][734][735][736][737][738]…”
Section: Discussionmentioning
confidence: 99%
“…Computer-assisted protein database search revealed six human proteins with high local sequence similarities with the HCV polyprotein: three nuclear proteins, namely, histone H2A.Z [22], matrin 3 [23] and replication protein A [24] and three smooth muscle proteins, namely, smooth-muscle myosin [25], vimentin [26] and smoothelin [27]. Of the nuclear proteins, histone H2A.Z and matrin 3 serve as structural components within the nucleus, while replication protein A is involved in DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…18 Using primers to specifically amplify transcripts for SM1 and SM2, myosin heavy chain isoforms that are different at the Cterminal region, 19,20 we found that the CSMC expressed predominantly SM1. The analysis of myosin light chain transcripts indicated that the cultured CSMC had a light chain pattern consisting of 74% LC17b, which is smooth muscle-specific, and 26% of the LC17a isoform, which is expressed by both smooth muscle and non-muscle cells in humans.…”
Section: Characterization Of Human Csmcmentioning
confidence: 91%
“…5,6 It generates a chimeric mRNA transcript, CBF␤-MYH11, by fusing the CBF␤ gene located on band q22 of chromosome 16 7,8 and the MYH11 gene, which encodes a heavy chain of the smooth-muscle myosin protein, located at the p13 breakpoint. 9,10 Messenger RNA analysis by reverse transcription-polymerase chain reaction (RT-PCR) can help define leukemic subsets and provide potentially valuable diagnostic and prognostic information. 11 Qualitative RT-PCR reveals the presence of detectable levels of minimal residual disease (MRD) in patients in complete clinical remission (CR) after induction chemotherapy.…”
mentioning
confidence: 99%